Polska tkanina artystyczna i użytkowa drugiej połowy XX w. ze szczególnymuwzględnieniem lat 70. - Błaszczyńska, Julia (Człowiek i Społeczeństwo, 2017)
Polish artistic textiles of the second half of the twentieth century are an important part of European art. The 1960s and the beginning of the 1970s was the “golden age” of artistic textiles. The most important researcher in this field was Professor Irena Huml who had published such works as: “Polish Applied Arts” and “Contemporary Polish Textiles”. As a result of the development of Polish textiles in the post-war era, the division of pure art and utilitarian art ceased to exist. The role of designer and the role of craftsman coexisted in the Polish artist during the time as capital restraints forced the designer-craftsman to experiment, something unique to Poland and not seen in other capital-rich countries. The blending of these roles – designer and craftsman – propelled Polish art to the top. Biennale Internationale de la Tapisserie was the most important textile event in Europe for the development of artistic textiles. An analysis of these exhibitions could help generate a general view of this field of art. The 1970s was underestimated because of quantity of phenomenon in the textile field: the organization of outdoor weaver workshops, the collaboration with the biggest Polish companies, Orbis and Lot for example, and, finally, the creation of a new type of artistic textiles: miniatures. Given that Polish artistic textiles of the 1960s and 1970s are underestimated and rarely researched, this study can be interesting and provide topics for original investigation. Julia Błaszczyńska, Polska tkanina artystyczna i użytkowa drugiej połowy XX w. ze szczególnym uwzględnieniem lat 70. [Polish artistic and utilitarian fabric of the second half of the twentieth century, with particular reference to the 1970s], edited by W. Bryl-Roman, „Człowiek i Społeczeństwo” vol. XLIII: Projektowanie w latach 70. [Designing in the 1970s], Poznań 2017, pp. 145-164, Adam Mickiewicz University. Faculty of Social Sciences Press. ISSN 0239-3271.